Efficacy of dental pulp stem cells from deciduous teeth in treating diabetic wounds / Pukana Jayaraman - Pukana, Jayaraman (2016)
Diabetic foot ulcers (DFU) are one of the common complications in diabetes mellitus (DM). The underlying problems of DFU are delayed wound healing due to hyperglycemia, poor blood circulation, and nerve damage. Mesenchymal stem cells (MSCs) from various sources including dental-derived stem cells have been used in studies in wound healing. The aim of this study is to assess the wound healing ability of human extracted deciduous teeth in both in vitro and in vivo model in different culture conditions and dosages. The immune gene expression of dental pulp stem cells from three different dental sources, namely human extracted deciduous teeth (SHED), periodontal ligament (PDLSCs), and dental pulp stem cells (DPSCs) were assessed in early and late passage. All three sources exhibited indistinguishable mesenchymal stem cell characteristics. Although SHED has increased immune gene expressions compared to DPSCs and PDLSCs, it is more suitable for clinical usage in its early passages than prolonged passages. This has led to investigations on biological molecules secreted by SHED cultured in low serum culture conditions in two different passages which are passage 2 (P2) and passage 4 (P4). Our findings show that at low serum concentrations, the expression of growth factors and cytokines were higher and had significant differences. The overall expression of genes, namely IL1B, IL2, IL4, IFNG, CXCL5, CD40LG, and CCL7, show increased expression in P2 low serum conditions. The percentage of wound closure in in vitro study of wound healing showed enhanced wound closure rate for SHED P2 2% FBS. The further study on enzymatic and nonenymatic antioxidants reported higher Superoxide Dismutase (SOD) and Total Glutathione (GSH) and decreased Malondialdehyde (MDA) and Advanced Oxidation Protein Products (AOPP) level in SHED treated group. The safe dosage for SHED was studied and it showed that there is no damage to liver and kidney in Sprague Dawley rats after the transplantation of SHED in two different dosages. After that, the wound healing rates on diabetic Sprague Dawley rats’ skin were studied on day 5 and 10. The histology of granulation tissue indicates that SHED has high collagen content and a thinner epidermal layer. Immunohistostaining presented an over-expression of Heatshock protein (Hsp70) marker which indicates higher wound healing rate in SHED treated group. The SOD activity and GSH level was amplified in the SHED-treated group with declining levels of MDA and AOPP. The hydroxyproline accumulation was augmented in the SHED-treated diabetic wound. The diabetic animal wound model was a pre-clinical study and is important in conveying SHED for therapeutic usage. The parameters induced by SHED in treating diabetic wounds are an increase in antioxidants level, reduction of lipid peroxidation and protein oxidation, accumulation of hydroxyproline, augmented expressions of the Hsp70 marker, promotion of the angiogenesis process through expression of wound repair genes, greater collagen deposition, and fewer inflammatory cells.